Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2018)
Surgical Management of Rhegmatogenous Retinal Detachment: A Meta-Analysis of Randomized Controlled Trials Soni C, Hainsworth DP, Almony A Ophthalmology 2013; 120: 1440-7. Corneal Collagen Cross-linking with Riboflavin and Ultraviolet A Irradiation for Keratoconus Hashemi H, Mohammad Amin Seyedian MA, Miraftab M, Fotouhi A, Asgari S Ophthalmology 2013;-120:-1515–20. Incidence of Canalicular Closure with Endonasal Dacryocystorhinostomy without Intubation in Primary Nasolacrimal Duct Obstruction Cannon PS, Chan WO, Selva D Ophthalmology 2013; 120: 1688-92. Detection of Glaucomatous Progression by Spectral-Domain Optical Coherence Tomography Na JH, Sung KR, Lee JR, Lee KS, Baek S, Kim HK, Sohn YH Ophthalmology 2013; 120: 1388-95.